Technetium-99 Conjugated with Methylene Diphosphonate Ameliorates Glucocorticoid Induced Osteoporosis by Inhibiting Osteoclastogenesis. (14th October 2018) - Shi, Lianjie; Ning, Ying; Xu, Liling; Li, Jianhong; Zhang, Xuewu
Abstract : Technetium-99 conjugated with methylene diphosphonate ( 99 Tc-MDP) is an effective anti-inflammatory drug in treating rheumatoid arthritis (RA) for over 15 years in China. However, as a special form of bisphosphonate, the antiosteoporotic effect of 99 Tc-MDP is unclear. We systematically investigated the effects of 99 Tc-MDP on cancellous and cortical bone, respectively, in glucocorticoid induced osteoporosis (GIO) animal models. Forty-eight Sprague-Dawley rats were randomly divided into six groups: blank, negative control, high dose, medium dose, low dose, and positive control groups. After dexamethasone was given to all groups except the blank group to induce osteoporosis, the rats in different groups were treated with saline, MDP, or different doses of 99 Tc-MDP. After treatment, all rats were sacrificed, and their tibiae and femora were analyzed with microcomputed tomography (micro-CT), histology and biomechanics. Micro-CT analyses showed that (1) 99 Tc-MDP reversed glucocorticoid induced bone microarchitecture destruction by increasing BV/TV, Tb.Th, and Tb.N and decreasing BS/BV, Tb.Sp, and TBPf; (2) effect of 99 Tc-MDP increased as its dosage increased; and (3) 99 Tc-MDP could improve cortical bone thickness while MDP failed to do so. Micro-CT spatial structure analysis and histology also yielded consistent results, indicating that 99 Tc-MDP increased trabecular number and connectivity morphologically. Secondly, biomechanics revealed that 99 Tc-MDP can enhance the extrinsic stiffness of bone by changing bone geometry. Finally, 99 Tc-MDP could inhibit osteoclastogenesis in PBMCs in human. In conclusion, 99 Tc-MDP exerted antiosteoporotic effect by improving both cancellous and cortical bone, as well as increasing extrinsic bone stiffness which might be attributed to the its inhibition of osteoclast differentiation. The antiosteoporotic effect of 99 Tc-MDP may suggest a potential clinical application for patients with GIO.